Coenzyme A biosynthesis and Coenzyme A-dependent redox processes as targets for anti-staphylococcal drug development - Moolman, Wessel Johannes Albertus (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.